THE DEVELOPMENT OF HIGHER EDUCATION OF PHYSICAL CULTURE FROM MOLDOVA IN THE CONTEXT OF EUROPEAN INTEGRATION - Viorica CALUGHER; Ecaterina LUNGU (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2016)
Purpose of Study: elaboration of diagnosis of the current situation of the physical education culture in Moldova and argumentation of a model of higher education strategic development in the context of the Single European integration. Hypothesis: Due to the diagnosis of the current higher education of physical culture (example: the State University of Physical Education and Sport of the Republic of Moldova) will be possible to draw up strategic development objectives and their implementation in the academic framework, in order the graduates to acquire professional skills required by the labor market and such, will be ensured its continued development in the context of European integration Research methodology includes: analysis and generalization of data, methodical and scientific sources, diagnosis. Findings and Results: The State University of Physical Training and Sport is a component of the higher education system from Moldova, which since 2005, joined the movement of university education reforming and its integration into the European academic area. The reforming of higher education of physical culture is determined by such factors as: specific national economic development, the requirements of the labor market, conditions of social integration through various professions, traditions of higher education in Moldova, transition to a knowledge economy, growing competition between national and European universities. In this context, there were implemented several educational reforms, such as: the cyclic organization of higher education of physical and developing of new curricula; ECTS system implementation; quality education insurance; establishment of quality management structures; policy-making and academic mobility programs.Conclusions and Recommendations: The development strategy of the higher education of physical culture and sports from Moldova is based on the following principles: achievement of a balanced profile education through decentralization; correlation of physical education system from Moldova with European educational systems; harmonization, compatibility of achieved skills with national and European market requirements; development of relationships between universities and businesses, culture, sport and civil society; changes planning and offering of a long enough time for answering, thus the universities are able to react to interventions caused by implemented new policies; encouragement of partnerships between higher education system components and / or those from the system of scientific research, beginning from a simple cooperation set of common goals, to complete merger in major educational and research institutions, able to cope increasingly strong competition from European or global education market.